Respons Al-Qur’an Terhadap Tren Childfree (Studi Analisis Kitab Al-Amthal fī Tafsīr Kitāb Allāh al-Munzal) - Salsabila, Siti Hadaynayah (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
The childfree trend is spreading with its controversies that contradict Indonesian cultural constructs and Islamic recommendations for procreation. The decision to be childfree needs to be addressed from the perspective of the Quran through interpretations of verses related to childfree, such as marriage and offspring, as the Quran is a guidance book suitable for every time and place. This research aims to find the Quran's view on the childfree phenomenon in the interpretation of al-Amthal and its implications. This research is qualitative in the form of a literature research. The method used is thematic analysis of key figures and descriptive analysis with an approach from the perspectives of feminism and Islamic law. The results of this study indicate that Makārim Shīrāzī's interpretation of childfree is not explicitly mentioned. However, his perspective emphasizes the importance of the presence of children and the significance of children as a gift from Allah. As for the implications of his interpretation on the childfree trend, it suggests that the Quran does not explicitly address childfree but instead underscores the value of having children as a means to draw closer to Allah. Therefore, it can be concluded that the decision to be childfree is permissible (considering various aspects), but it downplays the preference for having children.Keywords : The Quran, Child, Childfree, Tafsir al-Amthal